Molecular Analysis of Bacterial Meningitis in Suspected Cases - Jaleel, Lena K.; Umran, Mahfoodha A.; Kaddo, Khansaa B. J.; Ad'hiah, Ali H. (Iraqi Journal of Science, 2023)
One hundred and seventy-six cases of suspected meningitis (SMN) were included in a cross-sectional study. Their ages ranged from less than 1 year to 80 years, of whom 44.3% were male. The aim was to assess bacterial meningitis (BMN) in terms of incidence and types of causative bacteria. Cerebrospinal fluid (CSF) specimens were collected and polymerase chain reaction (PCR) analysis was conducted with universal primers designed to amplify a DNA fragment (996 bp) of the 16S rRNA gene of eubacteria. Resolving PCR products in agarose-gel electrophoresis revealed that 37.5% of CSF specimens were PCR positive, while 62.5% of CSF specimens showed no band and were considered PCR-negative. Eighty percent of the latter specimens were noted to have pleocytosis, in addition to having protein and/or glucose concentrations lower or higher than those in the normal range (abnormal CSF). The remaining 20.0% of CSF specimens were considered normal regarding pleocytosis, protein, and glucose (normal CSF). When the amplified DNA of PCR-positive specimens was subjected to sequencing and alignment with reference sequences, both Gram-negative (GN) and Gram-positive (GP) bacteria were identified (23 and 9 types, respectively). Acinetobacter spp. and Pseudomonas spp. were the most common GN bacteria (each with 17.8%), while Staphylococcus spp. was the most common GP bacteria (43.75%). The study concluded that BMN presents an important public health challenge, and PCR analysis of the CSF was an effective method for diagnosing pathogenic bacteria in SMN. In addition, leukocytes, glucose, and protein are valuable CSF parameters that may aid in the diagnosis of BMN.